2019
DOI: 10.21276/ijcmr.2019.6.6.57
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of CA19-9 and CA242 in Gallbladder Cancer - An Exploratory Study

Abstract: Introduction: There are, at present, no biomarkers to predict to prognosis of Gallbladder cancer. We conducted a prospective exploratory study to evaluate the role to serum CA 19-9 and CA 242 as prognostic markers. Material and Methods: We enrolled consecutive patients for this study and CA 19-9 and 242 were estimated from venous samples. Association of these markers with clinical variables and median overall survival (OS) difference between patients who has raised versus normal levels of these markers was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…[ 18 ] In contradiction Agarwal et al identified that with raised serum CA 19-9 and CA 242 levels median survival were less but was not statistically significant. [ 19 ] In the present study along with CEA and CA19-9, serum CA 125 levels were also evaluated as the prognostic marker to predict survival in GBC and similar to previous studies higher levels of tumor markers were found to be associated with poor overall median survival whereas contrary to previous studies CEA did not show a significant effect on the survival of GBC patients. Fang et al reported that preoperative CEA, CA125, and CA19-9 were associated with resectable cholangiocarcinoma whereas higher levels were associated with unresectable tumor.…”
Section: Discussionsupporting
confidence: 68%
“…[ 18 ] In contradiction Agarwal et al identified that with raised serum CA 19-9 and CA 242 levels median survival were less but was not statistically significant. [ 19 ] In the present study along with CEA and CA19-9, serum CA 125 levels were also evaluated as the prognostic marker to predict survival in GBC and similar to previous studies higher levels of tumor markers were found to be associated with poor overall median survival whereas contrary to previous studies CEA did not show a significant effect on the survival of GBC patients. Fang et al reported that preoperative CEA, CA125, and CA19-9 were associated with resectable cholangiocarcinoma whereas higher levels were associated with unresectable tumor.…”
Section: Discussionsupporting
confidence: 68%
“…These findings may be explained by the inclusion criteria, as in the present study, only early and suspicious cases of GBC were included. In accordance with this, a previous study by Agarwal et al [ 14 ] explained that CA 19-9 and CA 242 are not recommended as prognostic markers. By contrast, Agarwal et al [ 16 ] reported the prognostic role of tumor markers in terms of overall survival rate.…”
Section: Discussionmentioning
confidence: 55%
“…However, there was no association of tumor markers with the presence of gallstones and sex of the patient. In accordance with this, a prospective exploratory study conducted at a tertiary care center in Lucknow, did not find any association of CA 242 with tumor stage, presence of jaundice, gallstones and sex of the patient[ 14 ].…”
Section: Discussionmentioning
confidence: 73%
“…Our results were concordant to the reported literature where it has been found that CA19-9 and CA242 are significantly raised in GBC as compared to CC and HC. [18][19][20][21][22][23][24][25][26][27][28] The results displayed in table 5 clearly show that complimenting it with CA242 will not only add to specificity by which both may predict presence or absence of malignant change in gall bladder but also sensitivity while screening if we consider elevated levels of either of them inclusive.…”
Section: Discussionmentioning
confidence: 99%